Innovations in Arabic Language Learning: A Systematic Literature Review of Teaching Strategies and Technological Integration - Ainun Nufus, Nadia; Azis, Abdul (Pascasarjana Universitas Islam Negeri Mataram, 2025)
This systematic literature review examines innovative teaching strategies and technological integrations in Arabic language education, focusing on studies published between 2016 - 2025 from databases such as Google Scholar, Scopus and DOAJ. The findings highlight the effectiveness of methods like the Silent Way, elaboration strategies, thematic instruction, language immersion and the Direct Method in enhancing learners' vocabulary, reading and speaking skills. Additionally, the integration of digital technologies including e-learning platforms, mobile applications and AI-driven tools has been shown to boost learner motivation, engagement, and personalized learning outcomes. successful implementation depends on factors such as teacher readiness, infrastructure availability, and cultural adaptability, especially for non-native speakers. The study underscores the importance of comprehensive professional development and culturally responsive pedagogical frameworks to optimize the effectiveness of these innovations in Arabic language education.